The power of a whisper : hearing God, having the guts to respond - Hybels, Bill. (Grand Rapids, Mich. : Zondervan, 2010)
In The Power of a Whisper: Hearing God, Having the Guts to Respond, Bill Hybels reveals the attitudes and actions that help us hear directly from heaven as we navigate the most significant challenges on earth.
Fifty-year whisper-fueled odyssey -- Samuel's ear -- Our communicating God -- Evidence from everywhere -- How to know when you're hearing from God -- God's written whispers -- Light for dark nights of the soul -- Promptings for parenthood -- When God speaks through others -- Whispers that change the world -- Just say the word.
Includes bibliographical references (pages 271-273).
Keywords: Listening -- Religious aspects -- Christianity; Spirituality; Nonfiction